Cost-Effectiveness of Treating Upper Limb Spasticity Due to Stroke with Botulinum Toxin Type A: Results from the Botulinum Toxin for the Upper Limb after Stroke (BoTULS) Trial - Nick Steen; Gary A. Ford; Laura Graham; Michael Barnes; Frederike van Wijck; Christopher Price; Lisa Shaw; Phil Shackley; Helen Rodgers (Toxins, 2012)
Stroke imposes significant burdens on health services and society, and as such there is a growing need to assess the cost-effectiveness of stroke treatment to ensure maximum benefit is derived from limited resources. This study compared the cost-effectiveness of treating post-stroke upper limb spasticity with botulinum toxin type A plus an upper limb therapy programme against the therapy programme alone. Data on resource use and health outcomes were prospectively collected for 333 patients with post-stroke upper limb spasticity taking part in a randomized trial and combined to estimate the incremental cost per quality adjusted life year (QALY) gained of botulinum toxin type A plus therapy relative to therapy alone. The base case incremental cost-effectiveness ratio (ICER) of botulinum toxin type A plus therapy was £93,500 per QALY gained. The probability of botulinum toxin type A plus therapy being cost-effective at the England and Wales cost-effectiveness threshold value of £20,000 per QALY was 0.36. The point estimates of the ICER remained above £20,000 per QALY for a range of sensitivity analyses, and the probability of botulinum toxin type A plus therapy being cost-effective at the threshold value did not exceed 0.39, regardless of the assumptions made.